PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA PEGAWAI DUKCAPIL KABUPATEN NGADA - Godefridus R Sapu; Philipus Tule; Chosmas Fernandez; Vincent Gaspersz (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the partial and simultaneous influence of the physical work environment and work motivation on work discipline. This research method is a quantitative method with multiple regression analysis. The sample is 33 employees of the Population and Civil Registration Service of Ngada Regency. The results of this research partially show that the physical work environment has a significant effect on work discipline with a calculated t of 2,209 which is greater than the t table (2,209 > 1.697) and has a significance level of 0.035 < 0.05. Work motivation has a significant effect on work discipline with a t count of 7,300 which is greater than the t table (7,300 > 1.697) and has a significant level (0.000 < 0.05), while the results of the simultaneous test show that the f count value is 28.729 with a significance of 0.000, then fcount is 28.729 > 3.32 ftable with a significance of 0.000 < 0.05, so it can be said that there is a significant simultaneous influence of the physical work environment and work motivation of the work discipline of the Ngada Regency Population and Civil Registration Service employees, the magnitude of the influence of the variables of the physical work environment and work motivation on work discipline of 65.7%.